Axillary Artery Injuries Surgical experience review in a single vascular trauma center - Hamza, Bahaa I. (AL-Kindy College Medical Journal, 2020)
Background: Injuries to blood vessels are among the most dramatic challenges facing trauma surgeons because repair is often urgent, the surgeon has to decide between management options (open or endovascular), and gaining control and reconstructing a major arterial injury can be technically demanding . Objective:,To analyze the cause of injury, surgical approach, outcome and complications of axillary artery injuries. Methods A descriptive cross-sectional study on fifty patients at Ibn-Alnafees hospital in Baghdad from January 2005 to December 2010 Results Males were more commonly affected than female with ratio of 6.1:1. Most injuries were caused by bullet and shell (84%), followed by stab wounds (10%) and blunt trauma (6%). Patients were divided into three groups according to the involved part of the axillary artery: the first part, the second part and the third part. The second part represents most of the cases (48%), the third part account for (30%), while the least is the first part (22%). Resection and end to end anastomosis was done in 80% of the cases, lateral repair in 8%, graft interposition in 8 % and ligation in 4%. Conclusion: The outcome of the injury in this study was in general good. The morbidity of the patients due to nerve injury and wound infection still problem. Mortality due to associated injury and delayed presentation was 4% which is acceptable as compared with other studies.